Size dependency and potential field influence on deriving mechanical properties of carbon nanotubes using molecular dynamics. Issue 4 (July 2015) - Dilrukshi, K.G.S.; Dewapriya, M.A.N.; Puswewala, U.G.A.
Abstract: A thorough understanding on the mechanical properties of carbon nanotube (CNT) is essential in extending the advanced applications of CNT based systems. However, conducting experiments to estimate mechanical properties at this scale is extremely challenging. Therefore, development of mechanistic models to estimate the mechanical properties of CNTs along with the integration of existing continuum mechanics concepts is critically important. This paper presents a comprehensive molecular dynamics simulation study on the size dependency and potential function influence of mechanical properties of CNT. Commonly used reactive bond order (REBO) and adaptive intermolecular reactive bond order (AIREBO) potential functions were considered in this regard. Young's modulus and shear modulus of CNTs are derived by integrating classical continuum mechanics concepts with molecular dynamics simulations. The results indicate that the potential function has a significant influence on the estimated mechanical properties of CNTs, and the influence of potential field is much higher when studying the torsional behaviour of CNTs than the tensile behaviour.